Will the Release of Presale Housing moderate or exacerbate residential price volatility? - Taking Apartmemt complexes Units in Taichung City as an Example - Yang, Ho-Wen; Chuang, Chia-Yu (Technium Social Sciences Journal, 2024)
During periods of economic prosperity, increased profit opportunities lead to active transactions in the existing housing market and heightened consumer risk preferences. At this time, developers increase the launch of presale housing projects to expand business opportunities, indirectly filling the supply gap of existing homes and alleviating housing demand. However, in reality, prices in both the presale and existing housing markets mutually drive each other up, further delaying the stabilization of housing prices. Therefore, whether the launch of presale housing projects can alleviate the demand for existing homes and achieve the function of price moderation becomes a research-worthy question. This study aims to investigate whether the volume of presale housing projects moderates or exacerbates housing prices. We focus on the volatility of aggregate residential housing prices in Taichung City, Taiwan, using transaction data of monthly average prices for Apartmemt complexes Units (high-rise buildings and high-rise apartments) from August 2012 to June 2023. We employ the ARCH/GARCH models to analyze the impact of presale housing project volumes on housing price volatility. Stability and convergence indicate a moderating effect of presale housing project volumes on housing prices; otherwise, it indicates exacerbation. After model testing, this study selects the most appropriate model as the ARIMA(3,1,0)-GARCH(1,0) model. This study finds that during periods of economic prosperity, the volume of presale housing projects does not aid in stabilizing or converging residential housing prices; instead, it exacerbates market disruption.